Mental Health in low-and middle income countries (LMICs): Going beyond the need for funding - Alloh, Folashade T; Regmi, Pramod; Onche, Igoche; Teijlingen, Edwin van; Trenoweth, Steven (Health Prospect, 2018)
Despite being globally recognised as an important public health issue, mental health is still less prioritised as a disease burden in many Low-and Middle-Income Countries (LMICs). More than 70% of the global mental health burden occurs in these countries. We discussed mental health issues in LMICs under themes such as abuse and mental illness, cultural influence on mental health, need for dignity in care, meeting financial and workforce gaps and the need for national health policy for the mental health sector. We highlighted that although mental health education and health care services in most LMICs are poorly resourced; there is an urgent need to address issues beyond funding that contribute to poor mental health. In order to meet the increasing challenge of mental health illness in LMICs, there is a need for effort to address cultural and professional challenges that contribute to poor mental health among individuals. We have a notion that mental health should be integrated into primary health care in LMICs. Creating awareness on the impact of some cultural attitudes/practices will encourage better uptake of mental health services and increase the ease when discussing mental health issues in these countries which can contribute to reducing the poor mental health in LMICs.